Local Wisdom, Environmental Sensitivity and Disaster Anticipation in Improving Social Balance of Students in Junior High Schools - Sukidin; Rachmawati, Sela; Naim, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to analyze the influence of local wisdom, environmental sensitivity, and disaster anticipation on social balance in Jember Regency. This study uses a social theory that underlies that local wisdom, environmental sensitivity, and disaster anticipation can affect social balance. The research method used is a survey with cluster and stratified random sampling techniques on 50 respondents in Panti District, Jember Regency. The collected data were analyzed using SEM PLS by calculating the multiple linear regression values ​​of three independent variables (local wisdom, environmental sensitivity, and disaster anticipation) and one dependent variable (social balance). The results of the analysis show that local wisdom, environmental sensitivity, and disaster anticipation have a significant positive effect on social balance in Panti District, Jember Regency. The novelty in this study is that it can integrate three important elements of local wisdom, environmental sensitivity and disaster anticipation in one complete framework to improve the social balance of junior high school students in disaster-prone areas. The findings of this study enrich the theory of contextual learning based on local culture and broaden the understanding of disaster mitigation education at the junior high school level. The theoretical implications of this study are to provide a positive contribution to the development of social theory on the influence of local wisdom, environmental sensitivity, and disaster anticipation on social balance. While the practical implications are recommendations to improve local wisdom, environmental sensitivity, and disaster anticipation in order to improve social balance in Panti District, Jember Regency, East Java Province, Indonesia.